Behavior of indirect maximal oxygen uptake on users of the PROSA Program at Universidad de Antioquia, Medellín, Colombia (2011)
ABSTRACT: Objective: This research work sought to describe the behavior of maximal oxygen uptake (VO2max) in a population of adults who performed regular physical activity and classify the level of cardio-respiratory fitness. Methods: 819 results were analyzed with the estimated 2000-m VO2max test from 2001 to 2009 of 125 subjects who exercise regularly in the PROSA program at Universidad de Antioquia and were discriminated by decade and gender. Results: The results showed that VO2max reached its peak between 30 and 39 years of age in men (52.0 ± 2.5 ml * kg-1 * min-1) and women (42.9 ± 3.5 ml * kg-1 * min-1). There were significant differences between the VO2max of men and women and the decline in all age groups, except for those over 70 years of age. The VO2max of men in the study was maintained between the 70 and 90 percentiles, while that of women was between 70 and 80 percentiles. Conclusion: The decline in VO2max associated with age is different for men and women and it is different in almost all age groups.